Lookup tables in multi-language format for selection and display - Loh, Eugene Wei Tian. (2011)
With better technologies, the number of Internet user increases every day. Internet users come from all over the world. The languages we use might not be the same. Websites need to internationalise in order to stay competitive and relevant. However, there are many ways of implementing multi-language support and each has their own merits and demerits.